CONTRIBUTION OF TOTAL FACTOR PRODUCTIVITY IN ECONOMIC GROWTH RATE - Emre Biber, Ahmet (IJRDO - Journal of Social Science and Humanities Research, 2017)
The main source of growth rates of countries is the increase in total factor productivity (TFP), which is the amount of physical-human capital used in production and how these two factors are used together in the most efficient way. One of the most important determinants of economic performance is productivity growth. New theoretical approaches, together with the increase in the amount of investment, show that productivity increases contribute positively to the growth processes of developing countries in particular.